Maternal behavior predicts neural underpinnings of inhibitory control in preschoolers. Issue 6 (27th May 2018) - Swingler, Margaret M.; Isbell, Elif; Zeytinoglu, Selin; Calkins, Susan D.; Leerkes, Esther M.
Abstract: Separate lines of research have revealed that the rapid development of inhibitory control in the preschool period is closely tied to normative brain development and influenced by early mother–child interactions. One potential theory is that maternal behavior in the context of early interactions influences the neural underpinnings of inhibitory control in development, with implications for child behavior. The purpose of this paper was to examine whether maternal emotional support, measured during a mother–child problem‐solving game, predicted child neural responses (frontal‐central N2 event‐related potential) and behavioral performance (discrimination index, d′) in a go/no‐go task of inhibitory control in a large, diverse sample of mother–child dyads ( N  = 276) observed in children's last year of preschool (mean age = 56 months). Results of a structural equation model revealed significant direct effects from maternal emotional support to child right hemisphere frontal‐central N2 responses to no‐go (inhibitory control) trials; greater observed emotional support predicted larger N2 responses. Larger right hemisphere N2 responses to no‐go trials were also associated with better overall observed task performance ( d′) . A test of indirect effects from maternal emotional support to child observed performance via right hemisphere N2 responses was significant, suggesting that underlying neurophysiology is one mechanism through which maternal emotional support is associated with a child's rapidly developing inhibitory control behavior in the preschool period. This work joins a growing literature demonstrating that caregiver behavior within a "normative" range is an important environmental factor contributing to the development of neural processes supporting child functioning.